La psicología social como crítica: Continuismo, estabilidad y efervescencias tres décadas después de la “crisis” - Íñiguez-Rueda, Lupicinio (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This paper asks about the effects of the “crisis of social psychology” three decades after it began. Also, the paper offers a diagnosis of the contemporary situation of social psychology, which shows its little influence on the contemporary practices. The paper searches as well into the roots of this discipline, in order to find some support for a more coherent exercise with the implications of the critical period. Finally, the paper offers a description of “social psychology as a critique”, which is understood as a continuous questioning and problematization of any practices of knowledge production within social psychology.